A Study Of Investor Financial Behavior on Online Trading System in Indonesian Stock Exchange: E-Satisfaction, E-Loyalty, And E-Trust - Rohmad Fuad Armansyah (Journal of Economics, Business, and Accountancy Ventura, 2020)
The online trading system allows traders to enter orders directly into the system via electronic media immediately and directly. This condition will affect the level of customer satisfaction while increasing customer loyalty. This research examines financial behavior in terms of satisfaction, trust, and loyalty in the use of an online trading system in the Indonesian stock exchange. Data was collected through an electronic questionnaire for the Indonesia Stock Exchange investors using convenience sampling. As many as 255 respondent data were obtained and processed using PLS-SEM (Structural Equation Modeling-Partial Least Square) approach. The results show that financial behavior, e-trust, e-satisfaction have an effect on the creation of e-loyalty of online trading system users in the Indonesia Stock Exchange. This suggests that the online trading system providers must improve their system's perceived satisfaction, including the features of advice and support in making purchasing decisions.